(3JMQjQ GdeLSWis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdejhS GdMcjes ((3CUagGf s)
(3ChdgG (B:s
(3GdMeO ddg eHOC cd eHOC , hZGjI cd ZGjI hHYO , abO cfJ HQgI ef GdReGf , YGRekG Ydi Cf CMQQ dfaSi , hdSGFQ WdHg GdYde ef GdENhGf , cJGH GdeLSWi, GdefShH Edi HWdjehS GdbdhPi s
(3BNQgG (B:s
(3aEPG CJeefG LeY eG jZfi GdLGO SDGd ef hLhO eG jMJGL Edjg Edi hLhOg , hJUMjM eG jMJGL Edi JUMjMg adfNJe GdcJGH , hCbhd hEPG habfi Gddg JYGdi GGjVkG Ydi JeGe eG aUdJg hEfLGR eG hYOJg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HgG cKjQ ef GdLOGhd hGdQShe GdgfOSjIHChdgG Jedc SfI (B1110(3g`s
(3gPg GdfSNI GdJi Hjf CjOjfG efbhdI ef fSNI cJHJ SfI (B661(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs